Gender Social Norms among Internal Migrant Communities in South-West Nigeria - Silva, Asagba Omolola; Duruji, Moses Metumara; Chidozie, Felix; Osimen, Goddy Uwa (Journal of Ecohumanism, 2024)
This study delves into the complex relationship between migration, gender social norms, and child marriage within internal migrant communities in Southwest Nigeria. Existing research has demonstrated that the dynamics of child marriage and migration are intricately interwoven and contingent upon specific contextual factors. This relationship is further nuanced by the dual pressures of conflict and forced displacement, which can exert both upward and downward influences on child marriage practices. Drawing from the prevalence of child marriage across multiple boards, specific normative factors were identified, such as a girl’s chastity as a means to preserve family honour, a preference for male education and opportunities, the perception of girls as a financial burden leading to early marriage, and the societal view of girls primarily in roles as wives and mothers. These norms constrain girls’ participation in decision-making processes and reinforce their subservient roles. The intersecting impact of these social norms on poverty and prolonged insecurity contributes to the perpetuation of child marriage. Insights from studies on legalities surrounding the permissible age for marriage underscore the significant sway of societal norms in determining marriage timing. These insights provide a foundation for the development of interventions and policies promoting gender equality and safeguarding the rights of individuals affected by child marriage. Despite a growing volume of research on child marriage, there remains a research gap within humanitarian contexts, particularly migration. This study seeks to address this gap by exploring the complex interplay between migration, gender, and social norms in shaping child marriage practices, specifically within the Nigerian context.